Thermally Driven Dynamic Behaviors in Polymeric Vesicles. - Allen,ME; Sun,Y; Chan,CL; Paez-Perez,M; Ces,O; Elani,Y; Contini,C (Small, 2025)
Stimuli-responsive polymeric vesicles offer a versatile platform for mimicking dynamic cell-like behaviors for synthetic cell applications. In this study, thermally responsive polymeric droplets derived from poly(ethylene oxide)-poly(butylene oxide) (PEO-PBO) polymersomes, aiming to create synthetic cell models that mimic key biological functions are developed. Upon heating, the nanoscale vesicles undergo fusion, transforming into sponge-like microscale droplets enriched with membrane features. By modulating the temperature, these droplets display dynamic properties such as contractility, temperature-induced fusion, and cargo trapping, including small molecules and bacteria, thereby demonstrating their ability to dynamically interface with biological entities. The findings demonstrate the potential of our sponge-like droplets in synthetic cell applications, contributing to the understanding of PEO-PBO polymersomes' unique characteristics, expanding the capabilities of synthetic cell structures, and representing an exciting possibility for advancing soft matter engineering to cell-like behaviors.